Protected areas in Spain - González Yanci, María del Pilar (Espacio Tiempo y Forma. Serie VI, Geografía, 1994)
Among the wide range of scientific meetings, seminars, conferences and congresses that are held under the common denominator of Geography, it is not very usual to encounter the issue of nature protection. It is therefore very satisfying to see that the UGI had paid special attention to this issue at its 1994 Regional Gonference, because geography, or rather, geographers, ought to take an active part in the fight to conserve our natural heritage, which is being spoilt at a rate that, in the recent past, nobody could have imagined. This is leading us towards a very bleak future, in which the loss, in terms of standards of living, could be irreversible.